TRIGGERING OF SEISMICITY REMOTE FROM ACTIVE MINING EXCAVATIONS - Mckinnon S.D. (My University, 2006)
Observations of seismicity and ground control problems in the Sudbury mining camp have shown that late-stage (young) sub-vertical strike-slip faults are sensitive to small mining-induced stress changes. The strength-limited nature of stress measurements made in the region indicates that these structures are in a state of marginal stability. Numerical continuum models are developed to analyze the behavior of such structures. In the models, shear strain localizations (faults) evolve such that there is close interaction between the fault system, stresses, and boundary deformation. Fault slip activity in these systems is naturally sporadic and reproduces the commonly observed Gutenberg-Richter magnitude frequency relation. It is shown that a relatively minor disturbance to such a system can trigger significant seismicity remote from the source of the disturbance, a behavior which cannot be explained by conventional numerical stress analysis methodologies. The initially uniform orientation of the stress field in these systems evolves with increasing disorder, which explains much of the scatter commonly observed in data sets of stress measurements. Based on these results, implications for stress measurement programs and numerical stability analysis of faults in mines are discussed.
Keywords: TRIGGERING; MICROSEISMICITY; STRESS ANALYSIS; ROCKBURSTS; FAULT STABILITY